Challenges of temporary protection in Syria - Ann Maymann (Forced Migration Review, 2005)
Forced displacement is now a defining characteristic of Iraqi society and will remain so for years to come. Many have chosen to leave for neighbouring countries, particularly Syria and Jordan, but remain in a limbo of temporary protection.